ANALISIS UJI KADAR Î²-KAROTEN PADA BUAH PATIKALA (Etlingera elatior (JACK) R.M. SMITH) SEBAGAI ALTERNATIF SUMBER VITAMIN A DAN ANTIOKSIDAN - Harun, Andi Ifriany (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
The high level of pollution in Indonesia causes a large number of free radicals that have the potential to cause several diseases. To overcome this, antioxidantsare needed which function to prevent heart disease, anti-aging, strengthen the immune system, protect the nervous system, and nourish the eyes. One known antioxidant is - carotene. This study aimed to analyze the -carotene content of patikala fruit (Etlingera elatior (Jack) R.M. Smith) originating from Pangandaran (West Java) as an alternativesource of vitamin A and antioxidants. The form of research is experimental. The researchparameters were linearity test, detection limit and quantitation, system suitability test and determination of -carotene levels. Analysis of pure -carotene standard solution usingHPLC obtained the results that the maximum absorption occurred at max 450 nm, linearity (r) was 0.9999 or close to the value 1. Determination of -carotene content was carried out in duplicate and the retention time of patikala fruit was 8,564 minutes and 8,597 minutes, respectively. levels of -carotene obtained by 0.1 ppm or 10 mg/100 g, while the need for -carotene per day is 5-6 mg/100 g, consuming patikala fruit of 50 grams per day can meet the daily needs of -carotene.